The Crime of Forced Disappearance of People According to the Case Law of the Inter-American Court on Human Rights - Modollel González, Juan Luis (2009)
The present article intends to develop the constituent elements of the crime in the matter of forced disappearance of persons. All this in light of the case law of the Inter-American Court of Human Rights. In this way, this body deals with the applicable sources to determine the international responsibility of the State. Likewise, Inter-American case law emphasizes the obligation of the State-Party to define this crime in its domestic law in accordance with international standards. Consequently, the author emphasizes that the Inter-American Court of Human Rights has not limited itself to making recommendations of a general nature on the aforementioned subject but, on the contrary, has dictated guidelines referring both to the purpose that the repression of this crime as in relation to the structure (elements) that the criminal type of forced disappearance of persons must contain. Those criteria include: the protected legal good, the typical behavior, the active subject. Finally, it is affirmed that the IACHR qualifies enforced disappearance as a crime against humanity and thus ask whether it is aimed at Each State party, when typifying the enforced disappearance of persons, grants it the same nature, which is indicated in the Rome Statute.